The Effect Of Kepok Banana Consumption On Metabolic Biomarkers In Type 2 Diabetes Patients - Harsalim Harsalim; Samsualam Samsualam; Hasriwiani Habo (Jurnal Ners, 2026)
Type 2 Diabetes Mellitus (T2DM) is a major public health problem with a continuously increasing prevalence, requiring sustainable non-pharmacological management strategies. One potential approach is the utilization of local foods as nutritional interventions. This study aimed to analyze the effect of Kepok banana consumption as a local food-based nutritional intervention on metabolic biomarkers among patients with type 2 diabetes mellitus. This study employed a quasi-experimental design with a pre-test and post-test approach. The intervention consisted of routine consumption of ripe Kepok bananas at approximately ±150 grams per day during the intervention period. Metabolic biomarkers analyzed included random blood glucose levels, lipid profile (total cholesterol), and blood pressure. The results demonstrated that Kepok banana consumption had a significant effect on improving metabolic biomarkers (p = 0.000). The proportion of patients with controlled blood glucose levels increased from 25% to 80%. Additionally, the proportion of patients with ideal total cholesterol levels increased from 25% to 55%, while cases of high cholesterol decreased from 60% to 0%. Blood pressure outcomes also improved, as hypertension cases decreased from 30% to 0%. These findings indicate that routine consumption of Kepok bananas may serve as an effective, affordable, and sustainable non-pharmacological nutritional intervention for improving metabolic biomarkers in patients with type 2 diabetes mellitus.